Opposing effects on regulated insulin secretion of acute vs chronic stimulation of AMP-activated protein kinase - Nguyen-Tu, Marie-Sophie (2022)
Aims/hypothesis: Although targeted in extrapancreatic tissues by several drugs used to treat type 2 diabetes, the role of AMP-activated protein kinase (AMPK) in the control of insulin secretion is still debatable. Previous studies have used pharmacological activators of limited selectivity and specificity, and none has examined in primary pancreatic beta cells the actions of the latest generation of highly potent and specific activators that act via the allosteric drug and metabolite (ADaM) site. Methods: AMPK was activated acutely in islets isolated from C57BL6/J mice, and in an EndoC-βH3 cell line, using three structurally distinct ADaM site activators (991, PF-06409577 and RA089), with varying selectivity for β1- vs β2-containing complexes. Mouse lines expressing a gain-of-function mutation in the γ1 AMPK subunit (D316a) were generated to examine the effects of chronic AMPK stimulation in the whole body, or selectively in the beta cell. Results: Acute (1.5 h) treatment of wild-type mouse islets with 991, PF-06409577 or RA089 robustly stimulated insulin secretion at high glucose concentrations (p<0.01, p<0.05 and p<0.001, respectively), despite a lowering of glucose-induced intracellular free Ca2+ dynamics in response to 991 (AUC, p<0.05) and to RA089 at the highest dose (25 μmol/l) at 5.59 min (p<0.05). Although abolished in the absence of AMPK, the effects of 991 were observed in the absence of the upstream kinase, liver kinase B1, further implicating ‘amplifying’ pathways. In marked contrast, chronic activation of AMPK, either globally or selectively in the beta cell, achieved using a gain-of-function mutant, impaired insulin release in vivo (p<0.05 at 15 min following i.p. injection of 3 mmol/l glucose) and in vitro (p<0.01 following incubation of islets with 17 mmol/l glucose), and lowered glucose tolerance (p<0.001). Conclusions/interpretation: AMPK activation exerts complex, time-dependent effects on insulin secretion. These observations should inform the design and future clinical use of AMPK modulators.